Career Management: The Role of Career Counsellors in Building Strategic Partnerships Between Individuals and their Employers - Neault, Roberta A. (Canadian Journal of Counselling and Psychotherapy, 2007)
As career counsellors strive to bring their practices into the mainstream of business, there are many emerging career management issues that they could potentially address. This article reviews important changes in the world of work, including restructuring, displaced workers, survivors, continuous learning, and self-directed careers. It then explores the new roles that both individuals and employers play in a career development culture. Finally it addresses specific mainstream niches where career counsellors can serve, including dealing with the psychological impact of change; building a resilient workforce; career planning, exploration, and work search activities; and training managers as career coaches and mentors.